2004
DOI: 10.1016/j.intfin.2003.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Growth, financial development, societal norms and legal institutions*

Abstract: Do societal norms help to explain cross-country differences in financial development? We analyze whether societal norms, in addition to legal institutions, have an impact on financial development. In particular, we address the implications of the inclusion of societal norms on the analysis of the impact of financial development on economic growth. Our first conclusion is that societal norms indeed are important in explaining stock market capitalization, while this is not the case for the supply of bank credit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…For the USA, Beck, Lundberg and Majnoni (2006) also found a positive correlation between capital market development (measured by a dummy variable computed to reflect whether the market capitalization exceeds 13.5 % of GDP and economic growth). Conducting a large investigation in the financial literature, Garretsen et al (2004) found a causal relationship between economic growth and financial market development; a 1 % improvement in economic growth determines a 0.4 % rise of market capitalization / GDP ratio. A large strand in literature document that financial development is a cause of economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the USA, Beck, Lundberg and Majnoni (2006) also found a positive correlation between capital market development (measured by a dummy variable computed to reflect whether the market capitalization exceeds 13.5 % of GDP and economic growth). Conducting a large investigation in the financial literature, Garretsen et al (2004) found a causal relationship between economic growth and financial market development; a 1 % improvement in economic growth determines a 0.4 % rise of market capitalization / GDP ratio. A large strand in literature document that financial development is a cause of economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Updates and extensions have re-affirmed its main conclusions (see Hofstede, 1991). These data are used a lot in social and economic research (for example, see Garretsen et al, 2004;Licht et al, 2003;McGrath et al, 1992;Thomas and Mueller, 2000). The fact that the data are more than 30 years old is not a main concern under the assumption that culture changes very slowly over time.…”
Section: Cultural Values and International Differencesmentioning
confidence: 99%
“…For example, La Porta et al (1998) show that the legal system and Garretsen et al (2004) that cultural dierences inuence growth. However, beyond this potential omitted variable problem we may also face the conceptual problem entailed in the assumption of a homogeneous production function between, say, developed and less developed countries.…”
mentioning
confidence: 99%